Energy Performance Analysis of a Multi-Story Building Using Building Information Modeling (BIM) - Syed Shujaa Safdar Gardezi; Syed Haris Haris Ali; Raheel Fayaz; Huzaifa Hassan Shah (Journal of Sustainability Perspectives, 2022)
There is an enormous rise in building construction to meet serious demands of population increase. Besides its benefits, certain negative impacts on climate change and environments are associated with the built environment due to substantial energy requirements during operational phase. The current work aims to assess the energy consumption pattern of a residential facility based upon solar path analysis using simulation technique. A multi-story conventional building has been developed in a virtual 3D parametric environment using building information modeling. The BIM model was converted into the energy model using cloud computing. The energy model, at the proposed current orientation, was analyzed using insight 360 and solar energy analysis performed accordingly. Based upon the solar path analysis, the study observed that, at the present trajectory of solar path, provision of solar panels arrangements on 106,221 ft2 Photovoltaic panel area can produce the energy of 2,163,417 kwh/year with a payback period of 0.8 years.Keyword: Building Information Modelling, Energy analysis, Energy Optimization, Architecture 2030 Challenge